Closure to Influence of included angle and sill slope on air entrainment of triangular planform labyrinth weirs by M. Emin Emiroglu and Ahmet Baylar - Emiroglu, M. Emin; Baylar, Ahmet (Asce-Amer Soc Civil Engineers, 2006)
[Abstract Not Available]
Keywords: Aeration Performance